2007
DOI: 10.1007/s00248-007-9241-2
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Characterization of Diuron-degrading Bacteria from Lotic Surface Water

Abstract: The bacterial community structure of a diuron-degrading enrichment culture from lotic surface water samples was analyzed and the diuron-degrading strains were selected using a series of techniques combining temporal temperature gradient gel electrophoresis (TTGE) of 16 S rDNA gene V1-V3 variable regions, isolation of strains on agar plates, colony hybridization methods, and biodegradation assays. The TTGE fingerprints revealed that diuron had a strong impact on bacterial community structure and highlighted bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 47 publications
0
26
0
Order By: Relevance
“…PCR products were quantified with the DNA quantification fluorescence assay kit (Sigma-Aldrich, St Louis, MO, USA). Each sample weighing 300 ng were electrophoresed through an 8% polyacrylamide gel (TAE 1.25 Â , urea 7 M, Temed 0.06%, ammonium persulfate 0.0625%) as previously described (Batisson et al, 2007). Band patterns were analyzed using the GelCompare 4.6 software package (Applied Maths, Kortrijk, Belgium).…”
Section: Random Amplification Of Polymorphic Dna-pcr (Rapd-pcr) Fingementioning
confidence: 99%
“…PCR products were quantified with the DNA quantification fluorescence assay kit (Sigma-Aldrich, St Louis, MO, USA). Each sample weighing 300 ng were electrophoresed through an 8% polyacrylamide gel (TAE 1.25 Â , urea 7 M, Temed 0.06%, ammonium persulfate 0.0625%) as previously described (Batisson et al, 2007). Band patterns were analyzed using the GelCompare 4.6 software package (Applied Maths, Kortrijk, Belgium).…”
Section: Random Amplification Of Polymorphic Dna-pcr (Rapd-pcr) Fingementioning
confidence: 99%
“…Several Diuron-degrading bacteria have been isolated from different agricultural soils [12]- [14] and river waters [15].…”
Section: Introductionmentioning
confidence: 99%
“…Several diuron-degrading bacteria have been isolated from different agricultural soils (10,13,16,42,53) and river waters (1). Furthermore, it has been shown that different fungi, either obtained from various culture collections or freshly isolated from agricultural soils, are capable of degrading diuron (8,20,29,52).…”
mentioning
confidence: 99%